When Should a Patient with Statin-Induced Myopathy Be Re-challenged? A Case of Necrotizing Autoimmune Myopathy - Elena Obreja; Pamela Sequeira; Diana Girnita (Case Reports in Rheumatology)
Statins are notorious for causing myalgia and sometimes mild elevation of CPK (creatine phosphokinase). Herein, we present a case of necrotizing autoimmune myopathy induced by statins. The patient was on therapy with atorvastatin for about six years before she started developing myalgia and mild elevation in CPK that resolved after discontinuation of therapy. Since her cardiovascular risk was high and she had hypercholesterolemia, three months after CPK levels normalization, she was re-challenged with pravastatin. Few months later, she again presented severe myalgia, weakness, and elevated CPK levels. Hence, medication was discontinued, and she undergone an extensive workup for possible causes of inflammatory myopathies that revealed necrotizing autoimmune myopathy. Our case report offers an excellent source of “identification patterns” of muscular autoimmune disease which can be easily mistaken as common side effect of a drug.